GAMBARAN KEJADIAN POST OPERATIVE NAUSEA AND VOMITING PADA PASIEN SECTIO CAESAREA DENGAN SPINAL ANESTESI DI RUMAH SAKIT UMUM DAERAH LEUWILIANG - Andre Anditiawan; Amin Susanto; Tin Utami (Jurnal Cakrawala Ilmiah, 2023)
Spinal anesthesia is a regional anesthetic technique that is good for obstetric surgery, lower abdominal and lower extremity operations. Spinal anesthesia has several side effects, one of which is Postoperative Nausea & Vomiting (PONV). This study aims to describe the incidence of PONV (Post Operative Nausea and Vomiting) in patients with caesarean section with spinal anesthesia at Leuwiliang Hospital, Bogor Regency. This type of research is descriptive research. The sample in this study was 50 patients who underwent Sectio Caesarea surgery with spinal anesthesia taken using a purposive sampling technique. Data were analyzed univariately to determine the frequency and percentage of age, BMI, antiemetics and the incidence of PONV in caesarean section patients with spinal anesthesia at Leuwiliang Hospital, Bogor Regency. Of the 50 respondents who underwent Sectio Caesarea surgery with spinal anesthesia regarding systolic blood pressure, 33 people (66%) were in the 25-39 year age group, while 16 people were in the 18-24 year age group (32%), and the 40 age group. -54 years amounted to 1 person (2%). Most of the sample, 26 people (52%) had a BMI of 25-29.9 kg, 16 people (32%) had a BMI of 18.5-24.9 kg, and 8 people (16%) had a BMI <18.5. Based on the duration of surgery, it was found that all respondents, namely 50 people (100%) underwent surgery with a duration of ≥ 1 hour. Based on the antiemetic used, it was found that 40 people (80%) used ondancetron and 10 people (20%) used metoclopramide. Of the 3 patients who experienced PONV, 2 people were in the age group 25 - 39 years, and 1 person was in the age group 40 - 54 years, 3 people had a BMI of 25-29.9 kg and were using the antimetic Ondansetron.